Analisis Faktor Fundamental Terhadap Harga Saham Pada Perusahaan Manufaktur Di BEI Periode 2009-2011 - Happy Darmawan, Henriyanto Wijaya (Jurnal Akuntansi, 2014)
The Purpose Of This Research Is To Obtain Empirical Evidence That The Fundamental Factors Significantly Influence The Stock Prices Of Manufacturing Companies Either Partially Or Simultaneously For The Years 2009-2011.